Does national corruption encourage earnings management? A comparison of countries on the European and American continents (Contextus - Revista Contemporânea de Economia e Gestão, 2023)
We analyzed the effect of national corruption perceived by the population on earnings management. Our sample consisted of 3,239 companies from 38 countries located in four geopolitical regions of the American and European continents between 2012-2019, analyzed using regression with panel data. We found that increasing levels of perceived corruption implies an increase in earnings management practices. Behavior that does not occur in the same way when considering the different geopolitical regions, because it occurs only in Latin American, North America and the Caribbean, but is non-existent in the other regions. We provide evidence that the perception of national corruption is a trigger for managers to change accounting choices.